Aux origines de l’immigration marocaine en Midi-Pyrénées - Arthur Baylac (Les Cahiers de Framespa)
After World War II, immigrants to nowadays’ Midi-Pyrénées region mainly came from European countries, mostly Italy and Spain. With decolonization, the Garonne basin area received a migrant population from North Africa which is sometimes wrongly perceived as undifferentiated. In the case of Moroccan migrants, this population was superimposed upon an already existing Moroccan presence essentially consisting of students and workers, whose cohesion and solidarity are studied here. Triggered by the recruitment of colonial soldiers and workers, it was only later that this flow of North African migrants to France increased to proportions similar to those of the other main immigrant communities. Thus, the history of Moroccan immigration is defined in relation to the limits of kinship between two different immigrations in time. The available documentation about the regional Moroccan presence is still to be explored, but some of its elements highlight the role of tiny postcolonial Moroccan migrations in the development of the massive migratory flow which came after them starting in the mid-1960s. Another origin, more specific to Midi-Pyrénées, could be found in the settlement of French farmers repatriated from Morocco, who probably initiated a widespread recruitment of Moroccan agricultural workers.